HORMESIS EFFECT OF HERBICIDES SUBDOSES ON SUBMERGED MACROPHYTES IN MICROASSAY CONDITIONS - Peres, L. R. S. [UNESP]; Vechia, Della J. F. [UNESP]; Cruz, C. (Univ Federal Vicosa, 2017)
The goal of the study was to evaluate the effect of 2.4-D and clomazone doses on the growth of the submerged macrophytes Egeria densa and E. najas, in microassay conditions. Therefore, tests were conducted in a bioassay room at the temperature of 27.0 +/- 2.0 degrees C, photoperiod of 24 light hours and illumination of 500 lux. The apical fragments (shoot tips) of the macrophytes with 5.0 cm of length were transferred to test tubes with a 100 mL capacity, containing 70 mL of water. The tested concentrations were: 0.1; 1.0:3.5; 11.2; 36.5; and 118.0 mg L-1 and a control sample with seven replications. In the test with 2.4-D on E. densa. in the control sample treatment and the 0.1 mg L-1 treatment there was shorter length: at 1.0; 3.5; 11.2; 36.5 and 118.0 mg L-1 there was a relative increase of 90.6; 96.3; 91.6; 86.5 and 58.8%, demonstrating growth stimulation. E. najas behavior was similar to that of E. densa. In the test, with clomazone for E. densa, the greatest length occurred in the control sample treatment. At the concentrations of 0.1; 1.0; 3.5; 11.2; 36.5 and 118.0 mg L-1, there was relative growth of-25.8;-26.4;-31.7;-28.4;-37.7 and -45.0% respectively, showing herbicidal effect on the plants. E. najas behavior was similar, with lower growth at 11.2, 36.5 and 118.0 mg L-1. Sub-doses of the herbicide 2.4-D cause growth stimulation (Hormesis effect) in E. densa and E. najas, while clomazone causes herbicidal effect.
Keywords: growth stimulation; aquatic plants; environmental dynamics; pesticides